ROLE OF TRAFFIC SIGNS & SYMBOLS AS NONVERBAL COMMUNICATION IN ROAD ACCIDENTS: A CASE OF DISTRICT MALAKAND - Arshad Rehman, Dr. Sajjad Ali , Shafaq Manzoor , Muhammad Tauseeq Gulshan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
World Health Organization (2015) reported that 20-50 million people got injured and 1.5 million died in accidents in the world. The aim of this study was to find out the level of understanding of drivers about nonverbal communication. In this regard the researchers studied the understanding of them through traffic signs and symbols. For this purpose, the researchers based their study only on Mandatory instead of informative and regulatory signs and symbols. Survey research was used, while data was collected from 300 districts Dir Lower and Swat based drivers randomly through questionnaire. SPSS version 21 was applied for statistical analysis. Findings of the study explored that both the District drivers have poor understanding regarding roadside signs and symbols. The results disclosed that only 25% drivers hailing from district Dir lower, while more than 70% derivers belong to district Swat have understood and recognition of roadside signs and symbols. It is concluded that age and driving experience also the factors for lack of roadside signs and symbols in the area. It is recommended to the license issuing authorities to make sure tests for drivers for getting license to make sure recognition of signs and symbols as well as to overcome road accidents in the area.